2022
DOI: 10.1038/s41467-022-29265-w
|View full text |Cite|
|
Sign up to set email alerts
|

Selective optogenetic control of Gq signaling using human Neuropsin

Abstract: Gq proteins are universally important for signal transduction in mammalian cells. The underlying kinetics and transformation from extracellular stimuli into intracellular signaling, however could not be investigated in detail so far. Here we present the human Neuropsin (hOPN5) for specific and repetitive manipulation of Gq signaling in vitro and in vivo with high spatio-temporal resolution. Properties and G protein specificity of hOPN5 are characterized by UV light induced IP3 generation, Ca2+ transients and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 77 publications
(119 reference statements)
0
27
0
Order By: Relevance
“…Of note, UV light triggers Ca 2+ influx in a retinal-and transient receptor potential channel-dependent manner in several human cell types that lack the overexpression of any opsin isoforms (Bellono et al, 2013;Hu et al, 2017), which suggests that caution should be taken while interpreting this response as a potential contribution of exogenously expressed opsin. Regardless of the exact signaling mechanism of human OPN5, our experiments show that the chicken Opn5 has several advantages as an optogenetic tool for controlling G q signals, as it does not require additional retinal, is activable by visible rather than UV light, and respond with about 10 times higher light sensitivity than that of human OPN5 (Wagdi et al, 2022). In summary, we present cOpn5 as a blue light-sensitive opsin for rapidly, reversibly, and precisely activating G q signaling.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Of note, UV light triggers Ca 2+ influx in a retinal-and transient receptor potential channel-dependent manner in several human cell types that lack the overexpression of any opsin isoforms (Bellono et al, 2013;Hu et al, 2017), which suggests that caution should be taken while interpreting this response as a potential contribution of exogenously expressed opsin. Regardless of the exact signaling mechanism of human OPN5, our experiments show that the chicken Opn5 has several advantages as an optogenetic tool for controlling G q signals, as it does not require additional retinal, is activable by visible rather than UV light, and respond with about 10 times higher light sensitivity than that of human OPN5 (Wagdi et al, 2022). In summary, we present cOpn5 as a blue light-sensitive opsin for rapidly, reversibly, and precisely activating G q signaling.…”
Section: Discussionmentioning
confidence: 76%
“…Following the publication of a preprint version of this manuscript (Dai et al, 2022), a recent study reported that, following the preincubation of 2 μmol L −1 all-trans-retinal, human OPN5-expressing HEK 293 cells respond to UV light with an increase in G q -associated signals (Wagdi et al, 2022). By contrast, our data here and several previous studies establish that the Opn5 orthologs from humans and mice activate G i signaling under UV and blue light in the presence of additional retinal (Calligaro et al, 2022;Kojima et al, 2011;Yamashita et al, 2010;Zhang et al, 2020) (Figure 1C and D; Figure S1E in Supporting Information).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ChR2 with blue light restored regular antral contractions (albeit to a lesser degree than previous contractions). Similarly, another study examined motility effects of a mammalian neuronal tissue opsin (OPN5, activated by UV light and deactivated with red shifted light (>470 nm)) that leads to G q receptor activation (Wagdi et al., 2022). In the small intestine of mice with OPN5 under the control of the chicken β‐actin promoter, illumination with UV light led to increased intestinal contractions.…”
Section: The Sip (Smooth Muscle Cells Interstitial Cells Of Cajal And...mentioning
confidence: 99%
“…Finally, Philipp Sasse's group expanded the optogenetic toolbox for cardiac research demonstrating that the human coneopsin allows to control G i signaling in embryonic stem cell derived cardiomyocytes (Cokic et al). Thus, the three canonical G-protein pathways of the heart (Makowka et al, 2019;Wagdi et al, 2022) can now be investigated and their underlying kinetics precisely determined. Daniel Pijnappel's group characterized potential long term effects of optogenetic stimulation via channelrhodopsins (Ordog et al) and the groups of Christina Schüler and Leonardo Sacconi developed new methods and platforms for cardiac toxicity screening (Credi et al; Engel et al) which is one of the evolving cardiac research fields in which the use of optogenetic stimulation is becoming more and more standard (Klimas et al, 2016;Lapp et al, 2017;Rehnelt et al, 2017).…”
mentioning
confidence: 99%
“…Finally, Philipp Sasse’s group expanded the optogenetic toolbox for cardiac research demonstrating that the human coneopsin allows to control G i signaling in embryonic stem cell derived cardiomyocytes ( Cokic et al ). Thus, the three canonical G-protein pathways of the heart ( Makowka et al, 2019 ; Wagdi et al, 2022 ) can now be investigated and their underlying kinetics precisely determined.…”
mentioning
confidence: 99%